Pelaksanaan Haji Di Luar Bulan Dzulhijjah - Fajar Syarif (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2020)
This research has proven that the time of implementation of performing hajj that is exist now is raw so it is impossible to establish the the hajj performing beyond the predetermined time. It is based on the proposition exist, not only in the Qur'an but also in Hadith. In accordance with the object of study, the type of this study is a research of library (library research). Therefore, during the assessment, the argument that supports this paper and understanding construction process, are taken from books  or representative and relevant research with this study object